THE EFFECT OF THE SAFE-SPOT PROGRAM ON THE LEVEL OF SAFETY AWARENESS AMONG FACTORY WORKERS AT PT X SEMARANG - Septian Supriyono; Bachtiar Chahyadhi; Rici Riansyah (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
The rising incidence of workplace accidents in Indonesia indicates that the occupational health and safety (OHS) system is not yet optimal. PT X, a botanical extraction manufacturing company, faces complex hazardous conditions requiring a high level of safety awareness among its workers. However, low levels of safety awareness were observed among factory workers. One way to enhance safety awareness is through a proactive educational program called SAFE-SPOT. This study aims to analyze the influence of the SAFE-SPOT program on the level of safety awareness among factory workers at PT X Semarang. This study employed a quasi-experimental design with a pre-test post-test control group. The study population comprised 92 production workers at factory PT X Semarang. A sample of 58 workers was selected through purposive sampling and randomly allocated into two groups of 29 workers each. Data analysis utilized the Mann-Whitney U Test to determine the influence of the SAFE-SPOT program on safety awareness levels post-intervention in the experimental group compared to the non-intervened control group. The results demonstrate that the SAFE-SPOT program significantly improves safety awareness levels among factory workers at PT X Semarang.